Pelaksanaan program imunisasi BCG terhadap partisipasi masyarakat di Posyandu Seroja - Lubis, Yusuf Hanafi (TROPHICO: Tropical Public Health J., 2023)
The Directorate of Disease Prevention and Control, Ministry of Health of the Republic of Indonesia shows that 1.7 million children have not received complete immunization from 2014 to 2016.Â  (Objective) This study aims to determine the effect of community participation on the implementation of the BCG immunization program at Posyandu Seroja. (Methods) using a quantitative approach with a cross-sectional research design by taking a sample of 40 people, namely all parents of toddlers who came to the Seroja posyandu in total sampling by conducting interviews using questionnaires to obtain information related to the implementation of the BCG immunization program, data were analyzed univariately, bivariately and multivariately to obtain crude values and adjusted oods ratio. (Results) shows that community participation in Posyandu is 50%. There is a significant relationship between public invitation to join the Posyandu program and the implementation of the BCG vaccination program (p-value; 0.032(<0.05), AOR; 2.049, 95%CI;4.95-8.48). (Conclusion) is factors that can affect the running of the BCG immunization program at Posyandu Seroja with a precision value of 5% are inviting people to participate in posyandu, inviting other parents to come to the posyandu and babies have been immunized against BCG.